Evolution of deep ground settlement subject to groundwater drawdown during dewatering in a multi-layered aquifer-aquitard system: Insights from numerical modelling - Zeng, Chao-Feng; Wang, Shuo; Xue, Xiu-Li; Zheng, Gang; Mei, Guo-Xiong (Journal of hydrology (Amsterdam), 2021)
•A fluid–solid coupling numerical model is established to simulate a pumping test.•Measured groundwater drawdown and soil settlement are used to validate the model.•Evolution of deep ground settlement in dewatering is obtained by model calculation.•Location of the greatest settlement (LoGS) differs as the dewatering condition changes.•A good agreement is found between LoGS and the zero-drawdown location in the soil. When a foundation pit is under hydraulic connection with surrounding environment, foundation pit dewatering usually incurs a series of environmental problems such as ground settlement. Recent studies reveal that the greatest settlement induced by dewatering sometimes appears in deep aquifer but sometimes appears at ground surface. This indicates that the location of the greatest settlement (LoGS) due to dewatering is uncertain. To reveal the evolution law of LoGS subject to groundwater drawdown during dewatering, a fluid–solid coupling numerical model was established based on a practical dewatering test inside a foundation pit. Measured and computed distributions of ground settlement and groundwater drawdown around the foundation pit were compared. Further, extensive numerical simulations were conducted to clarify the evolution of LoGS under different dewatering conditions. If the dewatered aquifer is of strong hydraulic connection with the overlying aquifers, the dewatering-induced maximum settlement will initially appear at the top of the dewatered aquifer but quickly shift upward to the ground surface. If a poor hydraulic connectivity exists between them, the maximum settlement will always stay at the top of the dewatered aquifer. However, regardless of the hydraulic conditions in strata, a good agreement always exists between LoGS and the zero-drawdown location above the dewatered aquifer.